EPIDEMIOLOGICAL SITUATION OF DIPHTHERIA IN RUSSIA AND IN THE REGIONS OF THE RUSSIAN FEDERATION SINCE 2005 TO 2011 - T. N. Yakimova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The analysis of the incidence of diphtheria in the Russian Federation after the second revaccination of adults since 2005 to 2011 is presented. The level of the immunization and. the state of population immunity were studied. The high level of protection against diphtheria was established. It provides positive epidemiological situation against this infection in the country.